(untitled) (Avocetta, 2024)
Territory selection by birds of prey is an essential process influencing survival and productivity. For Golden Eagle Aquila chrysaetos, research in Europe has focused primarily upon migrating and high-density populations, and rarely on the territory selection in low-density populations. We analysed Golden Eagle breeding sites in Central Apennines (Italy), spanning from 29 sites in 1980 up to 38 sites in 2020, verifying in 4 different years (1980, 1990, 2000 and 2020) their status of occupancy or vacancy, through cross-checking data from available literature and field observations. In the chosen years, each site was characterized by land use and neighbouring distances variables, to individuate the presence of a possible common selection process. The different protection status of each area (unprotected or Natural/National Parks) was tested, assuming that habitat protection could have positive effects on Eagles’ territory selection. The so obtained panel data was statistically analysed by means of t-test, χ2 test and probit models. In one hand, Golden Eagles in the Apennines showed a continuous recolonization of territories, including seven previously vacant and two undiscovered sites. On the other hand, half of the vacant sites remain unoccupied. Our results suggest that Golden Eagles, in a low-density population, tend to minimize the effect of lower quality habitats by choosing a breeding territory which can guarantee low intra-specific interferences: 35% of 2020 breeding pairs have, at least, one nearby vacant territory. Depending on the quality of the available breeding habitat, Individual Adjustment Hypothesis (IAH) supports or replaces Habitat Heterogeneity Hypothesis (HHH).